Diseño de un procedimiento para determinar costos de calidad del procesamiento de queso en el taller de lácteos de la UDIV-Carrera Agroindustrias - ESPAM MFL - Andrade Silva, Gema Valeria (2015)
The aim of this research is to design a procedure to determine the quality costs in the production of cheese in the Teaching Dairy Unit for Research and Community work in the Agroidustry school of the Polytechnic School Manuel Felix Lopez of Manabi. It was analyzed a number of bibliographies that allow to substain the theoretical part of the research. Similarly the use of techniques such as interview, observation and record of processes allowed to know from the beginning of the workshop to the production flow. Therefore, a diagnosis via Delphi matrix was performed, obtaining expert judgment in the agroindustrial area to gain a better understanding of the productive chains, also the coefficient Kendall was applied, which generated 70 % concordance in the assessment by the professionals; Moreover it was searched in a checklits the INEN rules to get the graphical representation of the breaches within the cause and effect diagram. It was determined the production cost of $ 3.48 (US Dollars) per unit generated items such as raw materials, quality costs, utilities, and others were considered. Thus it was estimated that the evaluation values would help to determine a quality assurance. Finally an adaptable methodological approach to related areas, which serve as a guide for future research design.